(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The dosage buildup factors for gamma rays in air are thoroughly examined in this work using four different formulations: the linear, quadratic, Berger, and Capo forms. We compute the accumulation factors and analyze their behavior as a function of the number of mean free pathways, using isotope data and attenuation coefficients. At lower photon energy, the data indicate notable variances, especially between the linear and Capo forms; at higher energies, there is convergence. Furthermore, for photon energies of 0.04, 0.38, and 1.09 MeV under various stability classes and release heights (20 m and 100 m), we examine gamma doses as a function of downwind distance. The results offer important insights into gamma radiation and emphasize the significance of choosing suitable buildup factor formulations depending on photon energy.